Hubungan Regulasi Emosi dengan Penyesuaian Diri Siswa di SMA Don Bosco Padang - Zai, Mistari; Firman, Firman (YASIN, 2024)
Several studies conducted show that in reality students' adjustment has not been realized well, such as having difficulty interacting with other people, breaking school rules, not following lessons well. Initial observations carried out at Don Bosco High School in Padang, researchers found that many students still have low emotional control, such as fighting with friends, easily getting angry and not accepting mistakes made, fighting teachers, giving up and giving up easily when facing difficulties. feelings of low self-esteem resulting in withdrawing from society, blaming oneself or others when things do not meet one's expectations. This research aims to describe the relationship between emotional regulation and student adjustment at Don Bosco High School in Padang. This research uses quantitative methods with a correlational research type. The population of this study was 287 students registered in class Data collection in this research used a questionnaire on students' emotional regulation and self-adjustment. The data was processed using percentage analysis and to test and analyze the relationship between emotional regulation and student self-adjustment using the Pearson product moment formula. The research results show that the self-adjustment of Don Bosco Padang High School students is in the medium category with a percentage of 60.7%. Don Bosco Padang High School students' emotional regulation is in the medium category with a percentage of 41.1%. The results of the correlation analysis show a significant positive relationship between emotional regulation and students' self-adjustment in the Don Bosco Padang High School environment with a correlation coefficient of 0.640 with a significance value of 0.000.